Mechatronic designs for a robotic hand to explore human body experience and sensory-motor skills: a Delphi study. (18th June 2018) - Beckerle, Philipp; Bianchi, Matteo; Castellini, Claudio; Salvietti, Gionata
ABSTRACT: To bridge the gap between users' expectations and technological solutions, a better understanding of human body experience and sensory-motor skills is mandatory. This could pave the way towards a novel generation of robotic hands, which can be successfully employed in everyday life e.g. in prosthetics and assistive robotics. Available robotic hands are still far from matching the requirements of the corresponding experimental and real-world applications, e.g. fast motions might be achieved at the expense of accuracy. Knowledge of the users' sensory-motor skills can guide technical developments, e.g. prosthetic design processes. This paper presents design solutions developed in a Delphi study. Explorative questionnaires are prepared to acquire and elaborate expert opinions to improve the design of previously developed robotic anthropomorphic hands. By gathering and fusing expert opinions, novel robotic hand and wrist concepts specifically optimized regarding body experience and sensory-motor skill research are developed. In three rounds, experts with experience in robotic hand design and/or control analyze, develop, and rank solutions for mechanisms, actuators, and control, which result in overall design concepts. The technical concepts and implications resulting from the study are discussed considering psychological and biomechanical aspects. GRAPHICAL ABSTRACT: